RETRACTED: Development of the method for determining electrode location and placement on the patient’s body in the EIT - Aleksanyan Grayr; Kucher Artyom; Katsupeev Andrey (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001